Taḥlīlu al Kalimati al ‘Arabiyyati li Muhādaṡati al Lughawiyyati ‘inda al Talāmīżi fī Ma’hadi ‘Arafati li al Tarbiyyati al Islāmiyyati al Hadīṡati Sungai Penuh - Iqbal, Muhammad; Buska, Wahyudi (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
The objectives of this study are to: 1) see the mistakes of the students in using Arabic when speaking in everyday life, 2) take the wrong words in using Arabic by these students, 3) analyze the wrong Arabic words and look for the Arabic words that are wrong. right. The type of research used is field research with analytic descriptive qualitative methods, the data collected is the pictures of the words and not numbers. It can be concluded from the results of this study: 1) Arabic words that are wrong in speaking due to the environment, 2) The environment can influence loan words in Arabic which results in incorrect pronunciation such as قبيح